Außerordentlicher SPD-Parteitag 1971 in Bonn, 1. Teil; 18.11.1971 - 20.11.1971 (2010)
3. Verhandlungstag am 20. November 1971:<NZ>Hans de With, Protokoll Seiten 638 - 641, 00'01'' - 07'56'';<NZ>Willy Brandt, Protokoll Seiten 641 - 642, 08'10'' - 14'27'';<NZ>Annemarie Renger, Protokoll Seiten 643 - 644, 14'52'' - 19'16'';<NZ>Gerhard Jahn, Protokoll Seiten 644 - 646, 19'25'' - 24'49''.;